Overweight, hypertension and microalbuminuria in urban and rural Bangladeshi schoolchildren - Mohammad Majharul Islam Islam; Mohammad Benzamin; Ranjit Ranjan Roy; Abdullah Al Mamun; Muhammad Tanvir Ahmed; Mohammad Tariqul Islam; Rezwana Ashraf; Rezaul Karim; Kamal Hossen; Susmita Biswas; Sufia Khatun (Paediatrica Indonesiana, 2019)
Background The prevalence of childhood overweight and obesity has increased over the last two decades due to high caloric intake and decreased physical activity. The dramatic increase in the prevalence of overweight children occurred in conjunction with increasing prevalence of hypertension. Microalbuminuria is an early sign of damage to the kidney and cardiovascular system. Hypertensive, overweight children have an increased chance of microalbuminuria. Objectives To assess the prevalence of overweight, hypertension, and microalbuminuria in urban and rural school going children and contributing risk factors and associations. Methods This cross-sectional study was done in schoolchildren aged 6 to 16 years, from urban and rural areas, in Bangladesh, from September 2015 untill August 2016. Subjects’ weights, heights, and blood pressures (BP) were measured. Overweight and hypertension (HTN) statuses were determined with age-appropriate standardized charts. Subjects were divided into overweight and normoweight groups to evaluate risk factors for overweight such as family history (F/H) of obesity, F/H of HTN, daily physical outdoor activities, and monthly family income by comparative analysis. All overweight children were divided into hypertensive and normotensive groups in order to compare their fasting lipid profiles, urine microalbumin, serum creatinine, and random blood sugar. Results A total of 976 schoolchildren from urban (471, 48.3%) and rural (505, 51.7%) areas were included. Overweight was observed in 22.3% of the urban group and in 8.1% of the rural group (P<0.001). Hypertension was observed in 24.7% of overweight children and in 2.5% of normal weight children (P<0.001). Contributing risk factors for overweight were less physical outdoor activities, F/H of obesity, F/H of HTN, and higher family income (P<0.001). Microalbuminuria and random blood sugar were significantly increased in the overweight with hypertension group compared to the normotensive group (P <0.005). Conclusion Overweight is a health problem, noted especially in urban areas. Hypertension is also significantly increased in overweight children. Factors like F/H of hypertension, obesity, sedentary lifestyle, and higher socioeconomic status are significantly associated with overweight. Microalbuminuria and increased random blood sugar are also significantly higher observed in hypertensive overweight children compared to normotensive overweight children.